Geothermal Power Generation: Harnessing Electrical Energy Through The Organic Rankine Cycle (ORC) System - Zikri, Ahmad; Sumarna, Herlin; Hidayati, Baiti; Anwar, Zainuri; Putri, Fenoria; Zamheri, Ahmad; Negash, Semir M; Nasution, Gaizka Ghifari (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The research employs a thermodynamic simulation method using an Engineering Equation Solver (EES), relying on theoretical calculations. This method is integrated into a geothermal power plant, precisely focusing on geothermal source temperatures of approximately 95ºC. The investigation centers on the heat transfer process within a high-temperature heat transfer fluid from geothermal sources, conveying stored heat to the Organic Rankine Cycle (ORC) evaporator. Three specific working fluids, R134a, R11, and R22, examine working fluid selection for ORC at 95ºC. The results highlight the R11 organic fluid as an optimal compromise, excelling in two crucial criteria. Firstly, R11 exhibits the highest net mechanical power, = 34.81 kW compared to alternative fluids. Secondly, it boasts the best energetic efficiency of the cycle, registering = 16.01%, outperforming both R134a ( = 13.17%) and R22 ( = 12.64%). In summary, this study conducts a focused analysis of the energy aspects of an Organic Rankine Cycle (ORC) for electricity production using geothermal sources and organic fluids. Operating at a geothermal source temperature of 95ºC with a water flow rate of 80 lt/s and environmental conditions at 20ºC, the parametric study emphasizes the superiority of the R11 organic fluid. R11 emerges as the optimal choice, demonstrating the highest net mechanical power and superior energetic efficiency compared to alternative fluids, thereby contributing valuable insights to advancing sustainable and efficient energy technologies.